2011
DOI: 10.1111/j.1365-2788.2011.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between challenging behaviour, burnout and cognitive variables in staff working with people who have intellectual disabilities

Abstract: OverviewThis thesis is submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (Clin. Psy. D.) at the University of Birmingham. It is comprised of two volumes and includes a research study and reports of clinical work while on placement during clinical training.Volume I includes a literature review paper and an empirical paper. The literature review examines the literature on stress in staff who work with people with intellectual disabilities and challenging behaviour in order to address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 58 publications
7
73
1
2
Order By: Relevance
“…A similarly sized correlation (albeit non-significant because the sample was smaller) was reported by Mills and Rose. 134 However, although there was a small correlation between key worker ratings of controllability and severity of challenging behaviour, we found no relationship between controllability ratings and IQ, consistent with earlier studies. 135,136 Therefore, increased control cannot explain why more able service users were rated as more angry.…”
Section: Intellectual Abilitysupporting
confidence: 78%
See 1 more Smart Citation
“…A similarly sized correlation (albeit non-significant because the sample was smaller) was reported by Mills and Rose. 134 However, although there was a small correlation between key worker ratings of controllability and severity of challenging behaviour, we found no relationship between controllability ratings and IQ, consistent with earlier studies. 135,136 Therefore, increased control cannot explain why more able service users were rated as more angry.…”
Section: Intellectual Abilitysupporting
confidence: 78%
“…157,175 Within these complex organisations, staff groups function within hierarchies and a variety of environments. Challenging behaviour is stressful for staff, 22,134 but their ability to cope is a function of their perceptions of self-efficacy, 152 and can be influenced by organisational factors such as supervision and support. 205 An organisational climate that has a good 'person-environment' fit promotes better job satisfaction for staff and potentially better outcomes for clients.…”
Section: Beyond Crisis Interventionmentioning
confidence: 99%
“…In accordance, the findings of a systematic review that included fifteen studies from six countries, showed that the levels of burnout did not differ to a significant degree from those of the normative sample as described by Mashlach, with the exception of Depersonalization scores that were higher [29]. As far as factors and determinants of burnout of personnel in units for people with disabilities, challenging client behavior is the most frequently reported stressor [23, 30]. In addition, personality traits like neurotic behavior, extraversion and being very self conscious may be predictors of burnout, as is also lack of social support [31].…”
Section: Introductionmentioning
confidence: 67%
“…For example, Isaksson, Graneheim, Richter, Eisemann, and Åström (2008) detected that nurses who had been exposed to violence scored higher in burnout. Subsequently, other authors qualified this fact, indicating that this positive association occurred particularly with emotional exhaustion and cynicism (Chung & Harding 2009;Howard, Rose, & Levenson, 2009;Mills & Rose, 2011). Hensel, Lunsky, and Dewa (2012) stated that between 7% and 24% of the workers do suffer burnout or are at high risk of burnout due to aggressions experienced.…”
Section: Introductionmentioning
confidence: 94%